EFFICACY OF LEMONGRASS (Cymbopogon citratus) AND CLOVE (Syzygium aromaticum) SPRAY AGAINST SCABIES: AN IN VIVO STUDY - Surya Ananda, Ade; Saputra, Renaldi; Salsabila Risa, Putri; Jannah, Miftahul; Fachrunnisa, Tyas; Sucipto, Sucipto (Fakultas Teknologi Pertanian Universitas Brawijaya, 2026)
Scabies is an infectious skin disease caused by Sarcoptes scabiei and frequently complicated by secondary bacterial infections involving Streptococcus sp. and Staphylococcus sp. Lemongrass (Cymbopogon citratus) contains citral compounds effective as acaricides, ovicides, and antibacterial agents. Clove (Syzygium aromaticum) contains eugenol, which exhibits acaricidal, ovicidal, and antibacterial properties. This study aimed to evaluate the therapeutic potential of an herbal spray formulated from lemongrass and clove essential oil extracts against scabies under in vivo conditions. The experimental study employed five treatment groups with five replicates each. Twenty-five rabbits confirmed with S. scabiei infestation were allocated into: a positive control group (P+) treated with 5% permethrin cream, a negative control group (P–) receiving no treatment, and herbal spray treatment groups at concentrations of 2.5% (P1), 5% (P2), and 7.5% (P3), with essential oils combined at a 1:1 ratio. The herbal spray was applied twice daily for 14 days by uniform coverage of scabies lesions. Observations were conducted daily from day 0 to day 14, with data recorded on days 0, 7, and 14 using scab area reduction as the primary efficacy parameter. The results demonstrated that herbal sprays at 5% and 7.5% concentrations, which showed no statistically significant difference between them, achieved the greatest therapeutic outcomes with scab area reductions of 95.170% and 99.556%, respectively. These findings indicate that the lemongrass and clove herbal spray represents a promising, safer, and more effective alternative for scabies management.